Susceptibility effects of GABA receptor subunit alpha-2 (GABRA2) variants and parental monitoring on externalizing behavior trajectories: Risk and protection conveyed by the minor allele. (23rd March 2015) - Trucco, Elisa M.; Villafuerte, Sandra; Heitzeg, Mary M.; Burmeister, Margit; Zucker, Robert A.
Abstract: Understanding factors increasing susceptibility to social contexts and predicting psychopathology can help identify targets for prevention. Persistently high externalizing behavior in adolescence is predictive of psychopathology in adulthood. Parental monitoring predicts low externalizing behavior, yet youth likely vary in the degree to which they are affected by parents. Genetic variants of GABA receptor subunit alpha-2 ( GABRA2 ) may increase susceptibility to parental monitoring, thus impacting externalizing trajectories. We had several objectives: (a) to determine whether GABRA2 (rs279827, rs279826, rs279858) moderates the relationship between a component of parental monitoring, parental knowledge, and externalizing trajectories; (b) to test the form of this interaction to assess whether GABRA2 variants reflect risk (diathesis–stress) or susceptibility (differential susceptibility) factors; and (c) to clarify GABRA2 associations on the development of problem behavior. This prospective study ( N = 504) identified three externalizing trajectory classes (i.e., low, decreasing, and high) across adolescence. A GABRA2 × Parental Monitoring effect on class membership was observed, such that A-carriers were largely unaffected by parental monitoring, whereas class membership for those with the GG genotype was affected by parental monitoring. Findings support differential susceptibility in GABRA2 .